The economics of hydroelectric power - Edwards, B. K. (Brian Keith), 1954- (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2003)
This book simplified applications-oriented introduction to the sometimes complex problem of scheduling integrated hydroelectric facilities provides a well-written entry-point for a rich field.
Includes bibliographical references (p. 164-170) and index.
gau 23/01/14
Loans
Keywords: Hydroelectric power plants -- Economic aspects; Electric utilities; Dams -- Economic aspects